2008
DOI: 10.1289/ehp.10757
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Cardiac Arrest and Airborne Fine Particulate Matter: A Case–Crossover Analysis of Emergency Medical Services Data in Indianapolis, Indiana

Abstract: BackgroundPrevious studies have found particulate matter (PM) < 2.5 μm in aerodynamic diameter (PM2.5) associated with heart disease mortality. Although rapid effects of PM2.5 exposure on the cardiovascular system have been proposed, few studies have investigated the effect of short-term exposures on out-of-hospital cardiac arrest (OHCA).ObjectivesWe aimed to determine whether short-term PM2.5 exposures increased the risk of OHCA and whether risk depended on subject characteristics or presenting heart rhythm.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 26 publications
(38 reference statements)
10
66
2
Order By: Relevance
“…For sudden cardiac death, Rosenthal et al found an association between PM2.5 exposure and out-ofhospital cardiac arrests in Indiana. 21 On the other hand, Levy et al did not observe an association between PM10 and out-of-hospital primary cardiac arrest in Seattle and Washington. 22 In Japan, most of the research interest involving air pollutant epidemiology has focused on impacts on the respiratory system and we are aware of only a few reports that examined the association between air pollutants and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 93%
“…For sudden cardiac death, Rosenthal et al found an association between PM2.5 exposure and out-ofhospital cardiac arrests in Indiana. 21 On the other hand, Levy et al did not observe an association between PM10 and out-of-hospital primary cardiac arrest in Seattle and Washington. 22 In Japan, most of the research interest involving air pollutant epidemiology has focused on impacts on the respiratory system and we are aware of only a few reports that examined the association between air pollutants and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 93%
“…The case-crossover design was first introduced by Maclure 24 and is used increasingly in the literature to assess episodic events following short-term exposure to air pollution. 3,4,[7][8][9][10]25 In the case-crossover design, each individual experiencing a health event serves as his or her own reference; in other words, individuals act as their own control. Ambient air pollution is used as a proxy for personal exposure.…”
Section: Statistical Methodologymentioning
confidence: 99%
“…Epidemiological studies have found the time to trigger a cardiac event from exposure to PM 2.5 or ozone ranges from the day or previous day of onset to hours before onset. 4,7,9,10 Part of this inconsistent range of time to trigger is due to exposure time misclassification. This could be better handled by addressing the uncertainty in combining the disparate data sets such as OHCA recorded at the minute and continuous across space and air pollution data recorded hourly at fixed locations.…”
Section: Future Researchmentioning
confidence: 99%
“…129 -136 However, no clear pollution-related associations were observed in studies from a relatively clean metropolitan area, Vancouver, British Columbia, Canada, 137,138 or from a relatively large study in Atlanta, Ga. 139 Similarly, pollution-related associations have been observed with cardiac arrest in Rome, Italy, 140 and Indianapolis, Ind, 141 but not in Seattle, Wash. 142,143 The mixed results may reflect different PM compositions due to different sources or variations among the methods used.…”
Section: Cardiac Arrhythmias and Arrestmentioning
confidence: 99%